A Comparison of CT-Scan Output Doses and Doses Given to Kidney Stone Patients - Ronel Arida Missinychrista; Kadek Subagiada; Erlinda Ratnasari Putri (Lambung Mangkurat University Press, 2023)
Kidney stones are a disease which occurs in the urinary tract and are hard accumulations like stones that form along the urinary tract and can cause pain, bleeding, obstruction to the flow of urine or infection. Generally, the method of diagnosis given by doctors to patients with kidney stones is through a CT scan. However, so far it is not known how much radiation the patient receives during the CT scan procedure. Therefore, in this study an analysis was carried out regarding the comparison of the dose issued by the CT-Scan with the dose received by the patient on the CT-Abdomen examination, an analysis of the patient dose based on the SSDE value on the CT-Abdomen examination, and an analysis of the total dose received by the patient on CT-Abdomen examination. The data used in this study is data downloaded from the official website page of the